Review of contributions in systematics and taxonomy of the Alberto Manuel Brenes Biological Reserve (ReBAMB) (1981-2013) - Jorquera García, Ada Luz (2017)
A total of 82 systematic publications were analyzed between 1981-2013, for the Alberto Manuel Brenes Biological Reserve (ReBAMB), which is part of the Central Volcanic Cordillera Conservation Area (ACCVC). This Wild Protected Area is located in San Ramón, Alajuela, and Montes de Oro, Puntarenas, Costa Rica. The study compiles 169 new records of which 98 refer to new species. The analysis includes taxonomic data publications by kingdom, order, family, genus and species. In addition, bibliographical data of the language, country of origin of the journal and frequency of publications were examined.